A combined geophysical and lithological study on eruptive history and Quaternary lacustrine stratigraphy of a maar in Leizhou Peninsula, China - Chen, Cong; Zheng, Zhuo; Zeng, Li-Feng; Xiao, Fan; Tian, Li-Ping; Huang, Kang-You (Journal of palaeogeography, 2021)
As the second common type of volcanic vent on Earth, maar-diatreme volcanoes and their post-eruptive lacustrine sediments are a main focus of volcanology, palaeolimnology, palaeoclimatology and palaeontology. A number of maar-type volcanoes have been found in Leizhou Peninsula, South China, but little is known about their eruption processes and detailed stratigraphy of the post-eruptive sediments. We present a combined geophysical and geological analysis to study the eruptive history and post-eruptive sediment stratigraphy of a large maar, the elliptical (1.8 × 3.0 km 2 ) Jiudouyang (JDY) maar. The lacustrine stratigraphy revealed by drilling cores shows that the JDY maar lake has three major stages of evolution: (i) deep-lake sedimentary environment characterized by high autochthonous diatom productivity; (ii) shallow lake to swamp with very low water levels, characterized by a high total organic carbon (TOC) and abundant wood fragments; and, (iii) intermittent shallow lake and alluvial deposits composed of clay minerals and sand. The electrical resistivity tomography (ERT) values and lithological features are highly consistent, which clearly reveal the presence of ca. 50 m thick lacustrine sediments, directly underlain by a ca. 70 m thick basaltic lava rather than diatreme breccia in the crater. This infill sequence implies an alternation of eruption style from phreatomagmatic to Strombolian and/or lava flow, due to high magma flux and ascent rate of the Hainan Plume during the middle Pleistocene. The ERT data also reveal the initial phreatomagmatic crater floor at ca. 120 m depth. The initial crater had a large diameter/depth ratio (ca. 17), with an elongated shape (major axis to minor axis = 0.6), implying possible lateral vent migration during the eruption. A significant erosion under tropical weathering condition during the last few hundred thousand years, accounted for the large size of the maar crater. The study provides insights into the eruptive history and post-eruptive evolution of a large maar, as well as the spatial distribution of the lacustrine sediments.